2003
DOI: 10.1269/jrr.44.7
|View full text |Cite
|
Sign up to set email alerts
|

Different Radiation Susceptibility among Five Strains of Mice Detected by a Skin Reaction

Abstract: Published reports about skin reactions to radiotherapy, especially among breast-cancer patients, suggest that there are interindividual differences in the normal tissue response, and genetic factors are thought to be involved in this variation. An analysis of murine strain differences may reveal the mechanism of genetic factors in the extent of normal tissue damage from irradiation for several endpoints. The variation in the radiation susceptibility was observed when the skin of mice from strains A/J, C3H/HeMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…Radiosensitivity is also dependent on animal strain [26]. Given the complex interplays between physics and biology outlined above, even formal animal welfare guidelines do not provide actual numbers and simply state that doses should be minimized [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiosensitivity is also dependent on animal strain [26]. Given the complex interplays between physics and biology outlined above, even formal animal welfare guidelines do not provide actual numbers and simply state that doses should be minimized [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many preclinical oncology studies use SCID mice which have increased radiosensitivity and a defective DNA repair mechanism [26, 66]. Tumors derived from SCID mice are more susceptible to high doses of radiation than tumors derived from C3H mice [25], which may be related to endothelial biology [67].…”
Section: Introductionmentioning
confidence: 99%
“…The recipient mice were exposed to 11.5, 12.0, 12.5, 13.0 and 14.0 Gy 60 Co γ-radiation doses, and then, 24 h after irradiation mice were transfused with 5 million PBMCs from TS-injected mice (details provided under ‘Materials and Methods’), and subsequently monitored for survival for 30 days post-irradiation. CD2F1 mice are relatively radio-resistant [46, 47] when compared with BALB/c or C3H animals, as indicated by the absence of the commonly noted early wave of deaths (at ∼6 d) after irradiation with radiation doses as high as 15 Gy. Data shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Iwakawa et al reported that skin reactions begin from day 10 and reach a maximum at 20-25 d post-irradiation, using 20-60 Gy X-rays in five strains of mice. 25) Therefore, the detection of iNOS protein at 10-14 d suggests that the expression of iNOS is an early event of the skin reaction after X-ray irradiation. Since eNOS or nNOS expression was not detected in X-ray irradiated skin, the NO observed in X-ray irradiated skin is probably derived from iNOS.…”
Section: Discussionmentioning
confidence: 99%